Minimally invasive plate osteosynthesis (MIPO) of the humeral shaft fracture: Is it possible? A cadaveric study and preliminary report - T. Apivatthakakul (2018)
Minimally Invasive Plate Osteosynthesis (MIPO) has gained popularity with satisfactory clinical outcomes in the treatment of long bone fractures. MIPO for humeral shaft fractures, however, could be a surgically dangerous procedure because of the risk of radial nerve injury. An anatomical study was performed to evaluate the feasibility of MIPO for the humeral shaft fractures, and to study the relationship between the radial nerve and the plate with the forearm in full pronation and in supination. The study was performed on ten arms from five fresh cadavers. Two separate incisions, one proximal and one distal, were made in each arm with the forearm in full supination. A 9-hole narrow DCP was inserted into a tunnel using an anterior approach and fixed with 2 screws each on the proximal and distal humerus. The tunnel was then explored to identify the relationship between the radial nerve and the plate. No radial nerve compression or entrapment by the plate was found. The distance measured from the closest part of the plate to the radial nerve was 2.0-4.9 mm (average 3.2 mm). When the forearm was pronated, the radial nerve moved closer to the plate by a distance of 0-3 mm. The results of this study showed that it is possible to treat humeral shaft fractures by the MIPO method using an anterior approach. To reduce the risk of radial nerve injury, the forearm must be kept in full supination during plate insertion, and excessive force should be avoided during retraction of the lateral half of the brachialis muscle together with the radial nerve in the distal incision. The results of using this MIPO approach for humeral shaft fractures in 4 patients were also reviewed. © 2004 Elsevier Ltd. All rights reserved.